PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN HASIL BELAJAR IPAS SISWA KELAS III SDN 14/I SUNGAI BAUNG - Novita Fitriana; Mei Nurcahyanti; Dinah Mamila Hibatuullah; Resyarusyda Parandrengi (STKIP Subang, 2026)
The low learning outcomes of elementary school students in science is a problem that is still often found in the learning process. Based on the results of initial observations in grade III of SDN 14/I Sungai Baung, learning is still dominated by lecture methods so that students tend to be passive, less involved in learning activities, and have not been able to connect science concepts with problems in everyday life. This condition has an impact on the low achievement of student learning outcomes that have not met the established completeness criteria. Referring to the theory of constructivism and various previous research results that cite the effectiveness of Problem Based Learning (PBL), this model is considered relevant to increase active involvement and student learning outcomes through problem-solving-based learning. This study aims to describe the application of the Problem Based Learning (PBL) model and improve the learning outcomes of grade III students in SDN 14/I Sungai Baung. This study is a Classroom Action Research (CAR) that refers to the Kemmis and McTaggart model with stages of planning, implementation of action, observation, and reflection carried out in two cycles. The research subjects consisted of 24 grade III students of SDN 14/I Sungai Baung. Data collection techniques included tests, observation, and documentation, while data analysis was conducted quantitatively and qualitatively. The results showed that the implementation of the Problem-Based Learning (PBL) model improved student learning activities and outcomes in each cycle. In cycle I, learning outcomes improved compared to pre-action conditions, although the success indicators were not optimally achieved. After corrective actions were implemented in cycle II, the percentage of classical learning completion increased and reached the established success indicators. Furthermore, students demonstrated increased activeness, collaborative skills, and critical thinking skills during the learning process. Thus, the implementation of the Problem-Based Learning (PBL) model has proven effective in improving the science learning outcomes of third-grade students at SDN 14/I Sungai Baung and can be used as an alternative, innovative learning model to improve the quality of learning in elementary schools.